(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study explores the coping mechanisms used by casual employees at a multinational manufacturing company in Zimbabwe to improve their lived experiences. A purposively chosen sample of sixteen casual workers from a multinational manufacturing company in Zimbabwe participated in this qualitative study. Information on the coping mechanism used by the research participants to enhance their daily experiences was also gathered through semi-structured interviews. The coping mechanisms used by casual employees at a multinational manufacturing company in Zimbabwe were categorised into counter-productive work behaviours, organisational citizenship work behaviours and moonlighting. The study also found that some of the coping mechanisms that the casual employees used such as theft and sabotage are gross misconducts, which could amount to immediate dismissal. This study may be a useful tool for understanding the coping mechanisms used by resource casual workers to improve their experiences. The study may also help employment relations specialists to develop safeguards against coping mechanisms that harm the organisation.